Synthesis and Pharmacological Evaluation of 7-chloro-6-fluoro-2-(5-aminooxazol/thiazol-2-aryldenylamino)-benzo(1,3)thiazoles (Journal of Scientific Research, 2010)
New series of 7-chloro-6-fluoro-2-(5-aminooxazol/thiazol-2-aryldenylamino)-benzo (1,3)thiazoles (Schiff’s base)(5a-g, 6a-g) were synthesized from 7-chloro-6-fluoro-2-(5-amino-oxazol/thiazol-2-amino)-benzothiazole (4a-b). Structures of the compounds were verified by 1H-NMR spectra. The synthesized compounds were screened for in vivo analgesic and antiinflammatory activities. Some of the compounds showed moderate activities.Keywords: Benzothiazole; Schiff’s base; Analgesic activity; Antiinflammatory activity.© 2011 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved.doi:10.3329/jsr.v3i1.6166                J. Sci. Res. 3 (1), 121-128 (2011)